2014
DOI: 10.4319/lom.2014.12.407
|View full text |Cite
|
Sign up to set email alerts
|

Impact of collection container material and holding times on sample integrity for mercury and methylmercury in water

Abstract: Mercury (Hg) and methylmercury (MeHg) concentrations in streamwater can vary on short timescales (hourly or less) during storm flow and on a diel cycle; the frequency and timing of sampling required to accurately characterize these dynamics may be difficult to accomplish manually. Automated sampling can assist in sample collection; however use has been limited for Hg and MeHg analysis due to stability concerns during extended storage times. We examined the viability of using automated samplers with disposable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The automated sampler was retrofitted with a strainer and sample tubing made from Teflon and Isco ProPak TM disposable sample bags made of low-density polyethylene (LDPE). An evaluation of the LDPE bags to store East Fork Poplar Creek water for filtered and unfiltered Hg and MeHg analysis determined that differences between samples collected into PET bottles and filtered and preserved immediately and samples collected into the LDPE bags and filtered and preserved within 24 h (mean 11 AE 7% different) were similar to duplicate grab samples collected with PET bottles and preserved immediately (mean 7 AE 10% different) [45]. Concurrent grab and automated samples taken throughout the study during storm and baseflow periods verified the laboratory findings and are discussed in Riscassi et al [45].…”
Section: Stream Sample Collection and Discharge Measurementsmentioning
confidence: 99%
“…The automated sampler was retrofitted with a strainer and sample tubing made from Teflon and Isco ProPak TM disposable sample bags made of low-density polyethylene (LDPE). An evaluation of the LDPE bags to store East Fork Poplar Creek water for filtered and unfiltered Hg and MeHg analysis determined that differences between samples collected into PET bottles and filtered and preserved immediately and samples collected into the LDPE bags and filtered and preserved within 24 h (mean 11 AE 7% different) were similar to duplicate grab samples collected with PET bottles and preserved immediately (mean 7 AE 10% different) [45]. Concurrent grab and automated samples taken throughout the study during storm and baseflow periods verified the laboratory findings and are discussed in Riscassi et al [45].…”
Section: Stream Sample Collection and Discharge Measurementsmentioning
confidence: 99%
“…Two were conducted in summer (Su2013 ¼ 28-29 August 2013; Su2015 ¼ 17-18 September 2015) and one in We previously demonstrated that this autosampling method does not compromise sample integrity for our creek water. 20 Grab samples were collected by wading into the middle of the stream, triple rinsing the bottle with creek water, then lling and sealing the bottle for transport to the lab.…”
Section: Field Methodsmentioning
confidence: 99%
“…A separate sample for TSS was collected in a 2 L HDPE bottle. Samples were either processed immediately in the field or held on ice until returned to the lab for processing (max holding time of 8 h; (Riscassi et al, 2014)). Concurrent with water sampling, ambient water conditions were measured (temperature, specific conductance, pH, dissolved oxygen; Table S1).…”
Section: Methodsmentioning
confidence: 99%